Modified plastic damage model for steel fiber reinforced concrete - Tran, T.T.; Pham, Thong; Tran, D.T.; Ha, N.S.; Hao, H. (2024)
Steel fiber reinforced concrete (SFRC) structures have been widely adopted and attracted great research attention due to their excellent performance in resisting tension and flexure bending. However, the existing analytical and numerical analyses of SFRC structures rely mainly on the experimental data of material tests, thereby being suitable for a case-by-case basis. This is due to the lack of a general and reliable constitutive material model for SFRC, which analytically considers the fiber-dependent parameters such as fiber geometry, fiber stiffness, and interface properties of fibers and concrete matrix. This study presents an approach to modify the concrete plastic damage model to represent the SFRC material constitutive relations for simulating the structural behavior of SFRC. In this approach, the general procedure to integrate the bridging effect of fibers through the pull-out mechanism into the constitutive relation of SFRC was proposed. The comparison between the numerical and experimental results was conducted to verify the reliability of the proposed model. The results demonstrated the proposed model could well represent the material performance of SFRC and the numerical simulations could capture reasonably the effect of the volume fraction, geometry, and properties of fibers on the structural response of SFRC.